The Objective Dimensions in Prohibiting Interfaith Marriages: A Comparative Study in Judaism and Christianity (Islamic Sciences Journal, 2025)
The Objective Dimensions in Prohibiting Interfaith Marriages: A Comparative Study in Judaism and Christianity
Keywords: Interfaith marriage, Judaism, objective, dimension, Christianity, prohibition.